State of the Arts: An Exploration of the Effects of Spanish Colonization on Traditional Taino and Aztec Artwork (SCAFFOLD: A SHOWCASE OF VANDERBILT FIRST-YEAR WRITING, 2023)
This paper examines Caribbean Taino and Aztec artwork before and after the Spanish conquest, outlining these cultures’ post-colonization creative lapses and eventual resurgences. My research examines multiple methods and materials used for pre-colonization art and the many reasons for its creation. The essay also addresses Spanish methods for repressing indigenous artistic expression and the melding of cultural and artistic influences resulting from the Spanish occupation.For additional context, listen to the author's reflection on the piece below.